Determinants of food habits among peri-urban adolescents in Santa Maria, Bulacan - Maramag, Cherry Cristobal
This study determined the usual food habits of adolescents from the low income and medium to high income groups from Santa Maria, Bulacan and the influence of personal and environmental factors on these factors through a cross-sectional survey. A total of 216 high school students, from the 3rd and 4th year levels, were included in the study. Personal information and influence of environmental factors were collected through a self-administered questionnaire and 24-hour food recall method. The participants' height and weight were secondary data were obtained either from the school nurse or from the Physical Education teachers. The study showed that adolescents consume foods high in sugar, fat and/ or salt at all mealtimes, predominantly during morning snacks. Regression analyses showed that adolescents who ate with the family during supper was less likely to consume high-sugar and/or high-salt foods. Further, adolescents from the low income group, those who consumed morning snack with peers and those who cited affordability as reason for choosing foods were likely to eat high-sugar and/or high-salt foods during morning snack. The results imply that family, peers, school and community environment as well as price of foods influences the food habits of adolescents. These sectors should be mobilized to play more active roles in educating, promoting, reinforcing and supporting good nutrition and health practices among our youth.